Biodegradation of Fluoranthene Contaminated Soil by Different Combinations of Bacteria. Issue 1 (June 2020) - Wang, Mingzhe; Zhang, Haonan; Li, Guangchun
Abstract: In this study, different combinations of three fluoranthene degrading bacteria YN420, YN1, E420 complex microorganisms were constructed through orthogonal experiment, and applied to the biodegradation of fluoranthene contaminated soil to determine the optimal combination of complex microorganism. The results showed that the degradation rate of fluoranthene in a soil slurry of different combinations of complex bacteria was higher than that of three strains inoculated alone. The optimal combination ratio of complex microorganism was YN420: YN1:E420=2:1:1, and different ratios of complex microorganism could be enhanced to the bioremediation of fluoranthene in contaminated soil.